Association of circulating Notch1 and VEGF with flow-mediated dilation and aerobic fitness in healthy adults - Shepley Brooke R.; Lester Nick J.; Yacoub Lana H.; Bain Anthony R. (Translational Exercise Biomedicine)
Notch1 is a mechanosensitive endothelial receptor that responds to vascular wall shear stress. However, data on Notch1 activity in humans remains limited, particularly regarding its role in endothelial function.